EFFECTIVENESS OF FAMILY THERAPY APPROACH TO REDUCE SIBLING RIVALRY IN CHILDREN AGED 8-10 YEARS IN KABAT VILLAGE, BANYUWANGI : EFEKTIVITAS PENDEKATAN FAMILY THERAPY UNTUK MENGURANGI SIBLING RIVALRY PADA ANAK USIA 8-10 TAHUN DI DESA KABAT BANYUWANGI - Erma putri dwi ambarsari; Heriberthus Wicaksono; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2025)
The study was conducted to determine the effectiveness of the family therapy approach to reduce sibling rivalry in children aged 8-10 years in Kabat Village, Banyuwangi. This study used a quasi-experiment with a pre-test and post-test group design. This study uses purposive sampling techniques to determine the sample, the sample taken consists of 5 families who have 2 children aged 8-10 years with a close age gap who experience high sibling rivalry problems. The data collection techniques used were sibling rivalry questionnaires, observations, and interviews. The researcher used a data analysis technique with a statistical program for social sciences (SPSS) version 21 test. The results of the study show that